Estimation of driving mechanisms for oil reservoir using Material Balance (MBAL Software) “A Case Study of Libyan Oil Field - Naser, Madi; Azouza, Omar Ibrahim; Abousedrah, Faraj Meftah (Journal of Pure & Applied Sciences, 2021)
Material Balance (MBAL Software) is a software used for efficient reservoir development and helps the engineer better define reservoir drive mechanisms and hydrocarbon volumes. Natural forces in the reservoir that displace hydrocarbons out of the reservoir into the reservoir bore and up to surface. This paper estimates and compares of driving mechanisms using dynamic simulation in MBAL software and predictive material balance method after history matching of both of this model. Results from this paper shows functionality of MBAL in terms of history matching and performance prediction. The objective of this paper is to estimate water influx with identifying water influx model parameter and to estimate reservoir drive mechanism for (8) eight Libyan oil reservoirs. The simulator results show the reservoir pressure history curve is matching to the stimulation curve, this gives a good indication of the input data that has been entered to the model. The driving mechanism for all those reservoirs it comes from three natural forces, which are fluid expansion, PV compressibility, and water influx.